Distress intolerance and pain catastrophizing as mediating variables in PTSD and chronic noncancer pain comorbidity. - Sainero-Tirado, Gloria; Ramírez-Maestre, María del Carmen; López-Martínez, Alicia Eva; Esteve-Zarazaga, Rosa (De Gruyter, 2022)
Objectives: Several studies have demonstrated posttraumatic stress disorder (PTSD) and chronic pain comorbidity. However, there is a lack of research on the psychological variables that might explain their co-occurrence. We investigated the mediating role of distress intolerance and pain catastrophizing in this relationship. Methods: A moderated mediation model was tested. The sample comprised 114 individuals with chronic noncancer pain (90 women and 24 men; mean age, of 60.04 years [SD=9.76]). Results: Catastrophizing had a significant effect on PTSD. Distress intolerance mediated catastrophizing and PTSD, and pain intensity moderated this relationship. Conclusions: New insights are provided into the psychological variables that may explain PTSD and chronic noncancer pain comorbidity.
Keywords: Dolor; Angustia; Estrés (Psicología); Chronic noncancer pain; Distress intolerance; Pain catastrophizing; Pain intensity; Posttraumatic stress disorder